Evaluating Stakeholder Awareness and Prioritizing Applications of UAVs Technology for Construction Safety Management - Harshil Halvadia; Kashyapkumar A. Patel; Dilip A. Patel (Journal of Engineering, Project, and Production Management)
Recent technological advancements have presented opportunities for enhancing construction safety. Among these, unmanned aerial vehicles (UAVs) hold promising potential to revamp safety monitoring, inspection, and implementation. However, their adoption in the Indian construction industry remains nascent. Therefore, this study seeks to evaluate stakeholder awareness regarding the application of UAVs in construction safety management. The investigation unfolds in two phases: (i) evaluating awareness and (ii) prioritizing applications. For these purposes, the study surveyed and interviewed 108 project management consultants (PMCs), contractors, clients, and experts to evaluate their familiarity with UAV technology. Findings reveal that 74.07% of stakeholders possess some awareness of UAVs. Building upon existing literature, eight key applications for UAVs in construction safety were identified. Utilizing the Relative Importance Index (RII) method, these applications are prioritized based on stakeholder input, and a high level of correlation is observed among stakeholder’s viewpoints. Notably, safety audits emerged as the highest-ranked application. This valuable insight serves as an evidence base for promoting UAV adoption and fostering improved safety management practices in the Indian construction sector.